Tuning Immobilized Commercial Lipase Preparations Features by Simple Treatment with Metallic Phosphate Salts - José R. Guimarães; Diego Carballares; Paulo W. Tardioli; Javier Rocha-Martin; Roberto Fernandez-Lafuente (Molecules, 2022)
Four commercial immobilized lipases biocatalysts have been submitted to modifications with different metal (zinc, cobalt or copper) phosphates to check the effects of this modification on enzyme features. The lipase preparations were Lipozyme®TL (TLL-IM) (lipase from Thermomyces lanuginose), Lipozyme®435 (L435) (lipase B from Candida antarctica), Lipozyme®RM (RML-IM), and LipuraSelect (LS-IM) (both from lipase from Rhizomucor miehei). The modifications greatly altered enzyme specificity, increasing the activity versus some substrates (e.g., TLL-IM modified with zinc phosphate in hydrolysis of triacetin) while decreasing the activity versus other substrates (the same preparation in activity versus R- or S- methyl mandelate). Enantiospecificity was also drastically altered after these modifications, e.g., LS-IM increased the activity versus the R isomer while decreasing the activity versus the S isomer when treated with copper phosphate. Regarding the enzyme stability, it was significantly improved using octyl-agarose-lipases. Using all these commercial biocatalysts, no significant positive effects were found; in fact, a decrease in enzyme stability was usually detected. The results point towards the possibility of a battery of biocatalysts, including many different metal phosphates and immobilization protocols, being a good opportunity to tune enzyme features, increasing the possibilities of having biocatalysts that may be suitable for a specific process.